2017
DOI: 10.18203/2320-1770.ijrcog20173373
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of ultrasound with histopathology for retained products of conception in medically managed abortions

Abstract: INTRODUCTIONThe global abortion rate is estimated at 28 per 1000 women of reproductive age but varies within regions. Medical abortion uses an anti-progestin, mifepristone (RU486), followed by a prostaglandin (misoprostol). Medical abortion is preferred from four up to seven or nine weeks.1 WHO 2014 has laid down guidelines for dosage of mifepristone and misoprostol-Upto 9 weeksMifepristone 200 mg oral, single dose followed by misoprostol 800 mcg vaginal, buccal or sublingual single dose. From 9 to 12 weeks-mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…Another similar study by Matijevic et al [4] reported a 98% sensitivity and 33% specificity for the detection of RPOC using the predefined sonographic criteria (including the presence of a mass >10 mm with echogenic patterns in the endometrium and low resistive index on Doppler), while Chopra et al [11] reported sensitivity (92%), specificity (60%), PPV (87.3%), and NPV (71.4%) using the criteria of endometrial echogenicity alone (thickness was measured if echogenicity was normal). Esmaeillou et al [12] examined both color Doppler and gray-scale ultrasonography and used a variety of criteria to define RPOC; they found that while a criterion of endometrial thickness greater than 1 0mm gave a perfect (100%) sensitivity and NPV, the addition of color Doppler criteria improved the diagnostic accuracy overall.…”
Section: Discussionmentioning
confidence: 99%
“…Another similar study by Matijevic et al [4] reported a 98% sensitivity and 33% specificity for the detection of RPOC using the predefined sonographic criteria (including the presence of a mass >10 mm with echogenic patterns in the endometrium and low resistive index on Doppler), while Chopra et al [11] reported sensitivity (92%), specificity (60%), PPV (87.3%), and NPV (71.4%) using the criteria of endometrial echogenicity alone (thickness was measured if echogenicity was normal). Esmaeillou et al [12] examined both color Doppler and gray-scale ultrasonography and used a variety of criteria to define RPOC; they found that while a criterion of endometrial thickness greater than 1 0mm gave a perfect (100%) sensitivity and NPV, the addition of color Doppler criteria improved the diagnostic accuracy overall.…”
Section: Discussionmentioning
confidence: 99%
“…An Indian study reported the following values: sensitivity of 92%, specificity of 60%, PPV of 87.3%, and NPV of 71.4%. 16 …”
Section: Discussionmentioning
confidence: 99%
“…RPOCs is defined as persistence of placental or fetal tissue in the uterus following delivery, termination of pregnancy or a miscarriage 1,4 . RPOCs is common cause of PPH after uterine atony.…”
Section: Introductionmentioning
confidence: 99%